Tavoitteena sujuva arki kulttuurien välinen työ sosiaali- ja terveydenhuollon työyhteisöissä - Pitkänen, Pirkko; Niiranen, Vuokko; Keisala, Katja (Tampere University Press, 2017)
The growth of cultural diversity in Finnish social and health care workplaces challenges to develop not only ways of working and interaction but also organizational structures. Work communities as a whole are facing new challenges. The aim of this book is to help work communities develop well-functioning practices for intercultural work. Effective interaction between cultures provides the foundation not only for the well-being of staff and customers, but also for the financial success of the organization. The paper presents five action studies in the social and health care organization, which analyzed the abrasion points of everyday interaction, developed functional practices and corrective measures, and evaluated the effects of interventions. The aim of the project was to bring about structural reforms in support of inter-cultural work, since only the changes would become permanent.